Valorization of Coffee Pulp in the Production of Pleurotus pulmonarius in Rural Communities of Colombia (2023)
Coffee production generates large volumes of waste, which have the potential to cause pollution problems to soil and water and loss of biodiversity. Coffee pulp was used as a substrate for the production of the edible mushroom Pleurotus pulmonarius, a high protein content product (17.8% ± 0.84%). The spent mushroom substrate (SMS) resulting from fungus production showed a decrease in lignin (49.7% ± 12%), cellulose (33.7% ± 10.8%), and phenolic compound (87% ± 2%) content, which avoids contamination of soil and water bodies by them. Since the SMS still contains N (2.45%), P (0.20%), K (0.112%), Ca (0.320%), and Mg (0.106%), it has the potential to be used as a raw material in the production of a biofertilizer. This model reduces the environmental impact of the byproducts generated by small coffee growers and constitutes an alternative to combat hunger in rural communities and to achieve the sustainable development goal of zero hunger proposed by the United Nations